Sistem Informasi Ekstrakurikuler Berbasis Web Pada SMK Muhammadiyah Somagede - Annisa, Fia; Setyawati, Endang; Suparno, Agus (Mahesa Research Institute, 2023)
Extracurricular is an activity aimed at developing potential, talents and abilities outside the academic field that must be followed by students.The extracurricular registration process at SMK Muhammadiyah Somagede is currently still using conventional methods in the form of paper forms.In addition to this, the process of recapitulating student data from each extracurricular activity, which is still done manually. This process takes a long time because you have to check each formula sheet and also have a lot of risk of errors. It should be more efficient if it is done online using an information system that can simplify, save time and cost in the extracurricular selection process and the student data recapitulation process. The purpose of this system is the creation of an Extracurricular Information System that can speed up and make it easier for grade 10 and 11 students to make selections and make it easier to manage registrant data for each extracurricular.The benefit of this system is that it helps the Student Staff of SMK Muhammadiyah Somagede to process extracurricular information data and process student data and recap data on extracurricular registrants, for Class 10 and 11 students of SMK Muhammadiyah Somagede it is easier to get extracurricular information and the extracurricular selection process, for those in charge of extracurricular activities at SMK Muhammadiyah Somagede Makes it easier to get information on the schedule of extracurricular activities that are taught and student registration data, for the Principal of SMK Muhammadiyah Somagede and PCM Somagede Staff Makes it easier to get information from extracurricular activities and find out the comparison graph of the extracurricular activities that are most chosen by students, and as a medium to introduce STIKOM Yos Sudarso Purwokerto to the general public. In this case the system development method uses a prototype model. Based on the results of the benefit test, the average value of the Correctness value is 99.37%, the Usability value is 97.5%, the Efficiency value is 97.5% and the Reliability value is 99.12%. From the results of the benefit test, it can be concluded that the Web-Based Extracurricular Information System at SMK Muhammadiyah Somagede can be used to speed up the recapitulation process of extracurricular registrants